Evaluation of the outcome of osteoarthritis among patients undergoing total knee replacement - Shekhar Singal; Sunny Gupta; Rajnish Garg; Pankaj Kumar (Wolters Kluwer Medknow Publications, 2023)
Background: To assess the outcome of osteoarthritis among patients undergoing total knee replacement (TKR). Materials and Methods: One hundred and four subjects with one hundred and fifty-two cemented total knee arthroplasties have been analyzed in the current research. Functional assessment was carried out using the preoperative and postoperative Knee Injury and Osteoarthritis Outcome Score (KOOS) score and its five subscales: pain, other symptoms, function in activity of daily living (ADL), function in sport and recreation (Sport/Rec), and knee-related quality of life (QOL). Results: A significant improvement in the KOOS symptom score was seen with score grade changing to excellent from poor. The average postoperative KOOS symptom score occurred to be 89.9198, whereas the mean preoperative KOOS score was 30.7960 with a mean difference of 59.02385. The mean postoperative KOOS pain score was 94.6304 and the mean preoperative KOOS score was 18.4831 with a mean difference of 76.14731. A significant improvement in the KOOS pain score was seen with score grade changing to excellent from poor. Sixty patients of 104 (57.7%) had an excellent satisfaction level with a postoperative range of motion, twenty-eight patients (26.9%) had a good, eleven patients (10.6%) had a fair, and five patients (4.8%) had a poor satisfaction level with a postoperative range of motion. Conclusion: Surgery for a TKR is successful in reducing individuals' pain and restoring their functional ability. Preoperative expectations and KOOS subscale scores are factors in patients' satisfaction, which is determined a year following surgery.